Adulthood in Zimbabwean literature for children: an analysis of the representation of adult characters in Takadini (1997) by Hanson B, A visit to the Gods (1987) by N.S Sigogo and Tapiwa and the Kidnappers(1997) by G. Hozo - Manyiwa, Beverly (Midlands State University, 2014)
The study looks at the representation of adult characters in Zimbabwean Children’s literature. It mainly focused on the depiction of women from various geographical settings. Issues affecting the representation of women were therefore brought to light from a feminist literary perspective. Children’s literary works which include Hanson’s Takadini, Sigogo’s Visit to the Gods and Hozo’s Tapiwa and the Kidnappers were used as the basis of the research.